2014
DOI: 10.1002/ejlt.201400251
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of phytosteryl phenolates

Abstract: Phytosteryl phenolates occur naturally in many cereals and were successfully synthesized through a twostep chemoenzymatic process, as previously reported. They were also found to exhibit a system dependent antioxidant activity. Three model systems were employed in this study to shed light on the antioxidant activity and action mechanisms involved. The maintaining or enhancing of the antiradical capacity of phytosteryl phenolates in the DPPH assay suggested that these derivatives might be used as antioxidants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…4). Previous researchers stated that phenolic compounds in the samples were effective in inhibiting DNA strand scission (Singh et al 2010;Tan and Shahidi 2014;Xiao et al 2014). Also, the results showed that various extracts of NFRB and CFRB showed significant (P < 0.05) differences in their DNA damage protective effect ( Figs.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…4). Previous researchers stated that phenolic compounds in the samples were effective in inhibiting DNA strand scission (Singh et al 2010;Tan and Shahidi 2014;Xiao et al 2014). Also, the results showed that various extracts of NFRB and CFRB showed significant (P < 0.05) differences in their DNA damage protective effect ( Figs.…”
Section: Resultsmentioning
confidence: 83%
“…In the hydroxyl radical-induced DNA damage assay, the control plasmid pUC18 DNA was mainly composed of the supercoiled form (approximately 77.23%) in the absence of Fenton's reagent (lane 1 of Figure 3, control). Previous researchers stated that phenolic compounds in the samples were effective in inhibiting DNA strand scission (Singh et al 2010;Tan and Shahidi 2014;Xiao et al 2014). The addition of various extracts of NFRB and CFRB to pUC18 plasmid DNA and Fenton's reagent mixture provided protection to plasmid DNA, resulting in the retention of the native form (supercoiled form, lanes 3-10 of Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Hydroxyl radical generated by the Fenton reaction are known to cause DNA damage and yield fragmented forms. 18,29,55 The treatment of pUC18 plasmid DNA with Fenton's reagent directed the alteration of supercoiled DNA (native form) to open circular form and linear form (oxidative damaged DNA). In this study, the change of DNA conformation was evaluated by electrophoresis (Fig.…”
Section: Inhibition Of Hydroxyl Radical Induced Supercoiled Plasmid D...mentioning
confidence: 99%
“…The activity for free ferulic acid was also found to be higher than the radical scavenging activity of the alkyl ferulates. In an earlier study comparing the DPPH radical scavenging activity of the free acids and their sterol ester in ethanol, a higher activity was found for steryl caffeate, but a lower activity for steryl sinapate compared to the corresponding free acid . To conclude, the type of solvent influences the DPPH radical scavenging activity for esterified and free hydroxycinnamic acids.…”
Section: Resultsmentioning
confidence: 85%